Smart Vertical Farming Using IoT - Rajermani, Thinakaran; Sarasvathi, Nahalingham; Eng, Jing Hui (INTI International University, 2020)
The vegetable industry is one of the important industries in Malaysia. It provides food for people, creates jobs for rural community and generates revenue for economic development. However, in current years, vegetable industries in Malaysia could not fulfil the demand due to shortage of workers in the farms. Thus, in this paper, Smart Vertical Farming System (SVFS) using IoT was proposed. It is a green revolution using emerging Information and Communication Technologies, into farming field. The system was developed using waterfall model with qualitative approach. The system able to monitor soil humidity, grow light and temperature of the planting environment. Initially the system was tested together with traditional farming method by growing 2 different kind of vegetables. After nineteen days, vegetables grown under SFVS could grow much faster and produce more leaves. From the finding it shows the system able to help the farmer to increase the quantity and quality of vegetables and ensure that the market having enough stock with reasonable price.